2020
DOI: 10.1111/jch.13844
|View full text |Cite
|
Sign up to set email alerts
|

Drinking frequency modifies an association between salt intake and blood pressure: A cohort study

Abstract: Salt sensitivity is one of the crucial risk factors of hypertension. The aim of the present prospective cohort study was to assess the clinical impact of alcohol drinking on an association between salt intake and blood pressure. The present study included 451 employees at a pharmaceutical company in Japan who underwent annual health checkups in both 2017 and 2018. The main exposure of interest was self‐reported drinking frequency at their first checkups: rarely, occasionally, and daily. To assess the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…It is necessary to grope the planning of temperance and abstinence as a target of behavioral modification in social concerns. Yoshimura et al reported that alcohol consumption is associated with salt intake and BP, and salt sensitivity improved by reducing alcohol intake [ 23 ]. Salt intake was also excessive for the drinking group at hospitalization in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to grope the planning of temperance and abstinence as a target of behavioral modification in social concerns. Yoshimura et al reported that alcohol consumption is associated with salt intake and BP, and salt sensitivity improved by reducing alcohol intake [ 23 ]. Salt intake was also excessive for the drinking group at hospitalization in this study.…”
Section: Discussionmentioning
confidence: 99%